Penilaian kawalan lampu isyarat terpisah berbilang kaedah - Riza Atiq O.K. Rahmat,; Kasmiran Jumari,; Azmi Hassan,; Hassan Basri, (2003)
It is frequently observed that the queue lengths on the approach roads at a signalised intersection are imbalanced during peak hours and in many cases traffic marshall has to control the intersection manually. This problem is partly due to the inability of the conventional system to be optimised and to get the actual traffic demand. To overcome these two problems, the traffic control system developed in this project adopts vehicle actuated control, optimised control and traffic marshall emulation control during low, high and congested traffic demand respectively. The system utilised a video detection system as the sensor to detect the real traffic demand. Experimental data show that the control system. is found to reduce the sum of queue length 33% as compared to the conventional system. During congested period proposed system reduced queue length by 9% and delay by 10% as compared to manual control by traffic marshall